Interfacial electron accumulation for efficient homo-junction perovskite solar cells - Song, S; Moon, B; Hörantner, M; Lim, J; Kang, G; Park, M; Kim, J; Snaith, H; Park, T (Elsevier, 2016)
Here we study perovskite solar cells based on mesoporous alumina scaffold infiltrated and capped with a perovskite absorber layer, which are devoid of a discrete n-type electron collection layer. We employ ethoxylated polyethylenimine (PEIE) to modify the interface between the perovskite absorber layer and the metallic transparent fluorine-doped SnO 2 (FTO) electrode. Surprisingly, the PEIE interlayer obviates the requirement for the conventional dense-TiO 2 (d-TiO 2 ) compact layer (or organic fullerene layer), usually required to selectively extract electrons from the perovskite film. The self-organized PEIE interlayer produced a strong induced dipole moment at the perovskite-FTO interface, with our results indicating that electrons accumulate within the perovskite film at this interface. The resultant “n-type” contact region within the perovskite absorber layer, progressing to an intrinsic (i) region within the bulk of the perovskite layer, represents an n-i homojunction and favorably enables selective electron extraction at the FTO electrode. Resulting solar cells deliver current-voltage measured power conversion efficiencies (η) of over 15.0% and a substantial stabilized efficiency (η) of 9.1%. Although our solar cell performance remains lower than the highest reported efficiencies for perovskite solar cells employing discrete charge selective extraction layers, it indicates significant potential for “homo-junction” perovskite solar cells, once the metallic-to-perovskite contact is fully controlled. Additionally, our work identifies the potential impact of modifying the interface between the perovskite absorber and the subsequent contact materials with dipolar organic compounds, which may be applicable to optimizing contact at perovskite-semiconductor heterojunctions.